Can impersonal touch replace interpersonal touch? An investigation using the rubber hand illusion - Jaehyoung Bae; Christian Wallraven (PLoS ONE, 2025)
Our socio-emotional development and well-being critically depends on interpersonal tactile interactions, which are sensed by the skin through C-tactile (CT) afferents that respond to gentle, slow touch at typical skin temperatures. In the present study, we investigated whether impersonal touch would be able to provide similar pleasantness compared to interpersonal touch within a body-ownership illusion paradigm. To provide impersonal touch at similar parameters, we used a thermal probe kept at 32∘C (typical skin-to-skin temperature) compared to a flat hand as interpersonal touch. Both forms of touch were performed at CT-compatible speeds of 3cm/s by a male trained experimenter within a classic rubber hand illusion (RHI) paradigm in two counter-balanced within-participant conditions. A sample of N=45 healthy participants was tested and pleasantness ratings, touch deprivation, and the Need-For-Touch-Scale (NFT) were gathered. Overall, the illusion was similar in both touch conditions and, importantly, we found no statistically significant difference in pleasantness between interpersonal and impersonal touch. Interestingly, neither NFT scores, nor touch deprivation measures correlated with individual differences in the RHI and affective ratings. Our results suggest that impersonal touch with CT-optimal components provide a pleasantness and subjective illusion experience compared to interpersonal touch under the RHI paradigm.